How Has COVID-19 Affected Higher Education and Research in African Countries? - Jansen-van Vuuren, Ross; N'jai, Alhaji (International Higher Education, 2021)
COVID-19 has affected scientific research, teaching, and learning globally. In African low- and middle-income countries, this has been felt more acutely due to preexisting limitations such as poor internet access and dependence on international collaborators for equipment. The pandemic has also brought new challenges to African universities, including the diversion of substantial resources to COVID-19-related needs. Positive outcomes include recognition of the urgent need to address underlying challenges and innovative endeavors in some institutions.